Evaluation of the Adult Strabismus-20 (AS-20) Questionnaire Using Rasch Analysis - Leske, David A. (Invest Ophthalmol Vis Sci, 2012)
PURPOSE. To further refine the Adult Strabismus 20 (AS-20) health-related quality of life (HRQOL) questionnaire using Rasch analysis. METHODS. Rasch analysis was performed independently on the original AS-20 using the following steps: dimensionality, response ordering, local dependence, infit and outfit analyses, differential item functioning, subject targeting, and confirmatory dimensionality. RESULTS. Two subscales were present in each of the original AS-20 subscales, for a total of 4 subscales, which were labeled “self-perception,” “interaction,” “reading function,” and “general function.” Response ordering was appropriate for 3 of the subscales but required reduction to 4 response options for the fourth subscale. No notable local dependence was found for any subscale. As a result of fit analysis, 2 items were removed, 1 each from 2 subscales. No significant differential item functioning was seen for sex or age. The resulting 5-item self-perception subscale and 4-item reading function subscale are reliable and target the adult strabismus patient cohort appropriately. The resulting 5-item interaction subscale and 4-item general function subscale have less than optimal reliability. CONCLUSIONS. The AS-20 benefits from reduction to 4 subscales (self-perception, interaction, reading function, and general function) and reducing the response options in the general function subscale from 5 to 4 options. The refined AS-20 may prove to be even more responsive to HRQOL changes in adult strabismus following treatment or changes over time.